Perceptions of preschool teachers of the characteristics of gifted learners in Abu Dhabi: A qualitative study - Mohamed, Ahmed; Elhoweris, Hala (Frontiers in Psychology, 2022)
Considerable evidence supports that preschool education is a milestone stage for children. Nonetheless, systematic preschool gifted education programs rarely exist in public elementary schools. The current study explored the perceptions of 16 preschool teachers (general and special education teachers) from two public schools in Abu Dhabi, United Arab Emirates (UAE) regarding their views about various components of gifted education for preschool children. Qualitative analyses, using the inductive data analysis method, revealed several themes such as (a) the concept and identification of giftedness, (b) characteristics of gifted preschoolers, (c) preschoolers’ problem-solving skills, (d) the communication and social skills of gifted preschoolers, resources/services offered by the school to serve gifted preschoolers, (e) enrichment programs available for gifted preschoolers, (f) inclusive education for gifted preschoolers, (g) twice-exceptional preschoolers, and (h) governmental support. The results of this study may help advocate for infusing more services and programs related to the identification and education of gifted preschoolers in public schools. The findings identified the need to have an abundance of assessment tools and enrichment programs that can empower preschool teachers to cater for giftedness.